SPATIAL INEQUALITIES AND ELECTORAL PREFERENCES IN CENTRAL EUROPE (GEOgraphia, 2025)
This study describes the electoral implications of spatial polarization in Poland, the Czech Republic and eastern Germany. Empirically, it highlights the voting behavior of residents from selected territories as examples of disadvantaged regions in these three countries, and the conditions that shape such behavior. We explore whether these implications can be explained by argument on populist preferences in peripheralized areas. An analysis of the results of the last three elections to the Polish, Czech and German parliament was used. In each country, we selected two territorial units representing less developed areas and contrasted them with a socioeconomically privileged area and the nationwide results. In Germany and the Czech Republic, support for populist parties is well above average in the peripheralized regions studied, and low in the dynamically developing places. There is no single political force that exploits voter discontent in lagging areas. Depending on the prevailing cultural and socio-economic conditions, these forces may be more right-wing, more left-wing or even rather centrist. In Poland support for clearly populist parties in disadvantaged regions reaches similar levels as in the rich community. Political differences are primarily visible on the conservatism/liberalism axis.